2024
DOI: 10.3233/jpd-230229
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Digital Health Literacy in an Evolving Parkinson’s Disease Care System

Christine D. Esper,
Blanca Y. Valdovinos,
Ruth B. Schneider

Abstract: Digital health technologies are growing at a rapid pace and changing the healthcare landscape. Our current understanding of digital health literacy in Parkinson’s disease (PD) is limited. In this review, we discuss the potential challenges of low digital health literacy in PD with particular attention to telehealth, deep brain stimulation, wearable sensors, and smartphone applications. We also highlight inequities in access to digital health technologies. Future research is needed to better understand digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that neurosurgical patients, particularly those from marginalized racial, gender, or socioeconomic groups, have a limited understanding of procedure-associated risks [76][77][78]. Furthermore, inequities in access to digital health technologies and low digital health literacy pose a unique challenge to PD patients as this disease impacts cognition and disproportionately affects the elderly [79]. Multiple studies have found that low digital literacy is a barrier to the use of digital health resources, particularly in underrepresented racial or socioeconomic groups [80,81].…”
Section: Patient-level Interventionsmentioning
confidence: 99%
“…Numerous studies have shown that neurosurgical patients, particularly those from marginalized racial, gender, or socioeconomic groups, have a limited understanding of procedure-associated risks [76][77][78]. Furthermore, inequities in access to digital health technologies and low digital health literacy pose a unique challenge to PD patients as this disease impacts cognition and disproportionately affects the elderly [79]. Multiple studies have found that low digital literacy is a barrier to the use of digital health resources, particularly in underrepresented racial or socioeconomic groups [80,81].…”
Section: Patient-level Interventionsmentioning
confidence: 99%
“…Larger randomized controlled trials are needed to provide more robust results on effectiveness. In addition, consideration of factors that may affect the usability of the mHealth app, such as disease severity and digital literacy [22] of patients from the recruitment stage, would be useful to evaluate the potential for introducing this app to a broader PD population.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…What should be kept in mind is that many of these treatments could be delivered digitally. While digital health technology for PwPD is developing rapidly [18] (e.g. in the context of telehealth, deep brain stimulation, wearable sensors, and smartphone applications), health literacy may be lagging behind, yet is indispensable for adherence.…”
Section: Mental Perspectivesmentioning
confidence: 99%